(untitled) (Bangladesh Journal of Dental Research & Education, 2013)
A survey was conducted on dental surgeons perception of ethics concerning informed consent. Forty-six dentists employed in different private and government dental colleges and private dental clinics, responded to a questionnaire, which contained ten questions related to the ethics of informed consent. The Study revealed that the dentists were aware of legal and ethical issues related to informed consent, and majority of them relied on verbal consent (82.6%) rather than a written consent for any form of treatment. All the dentists (100%) agreed to the importance of informed consent for patients, and almost all the participants (97%) agreed that patients hold the right to refuse treatment or take legal action if they were not informed properly, although 19% of the participants did not consider failure in obtaining informed consent as an offence. Sixty-three percent of the participants did not agree to the notion that a written consent would make dentistry difficult while the remaining 37% feared that dentistry would be difficult if written consent was made mandatory. The survey also revealed that participants were keen to learn more about principles of medical ethics and felt ethics be taught more elaborately in the undergraduate level. In conclusion it was suggested that dentists should obtain a written consent for ethical reason or legal safeguard or at least keep a written account of the type of consent given by the patient. DOI: http://doi.dx.org/10.3329/bjdre.v2i2.16241 Bangladesh Journal of Dental Research & Education Vol.2(2) 2012: 31-35